They Call Us Problem Child: Delinquency, Medicalization, and Social Class in Primary Education. Issue 11 (1st November 2016) - Lavin, Melissa F.
ABSTRACT: This article recounts my seven-year struggle with my son in his high-performing school district, and his immediate shift in identity from delinquent to honor student when we changed districts. I argue that social class is encoded in setting and family form. Factors like context, class and family form discrimination, diagnosis in schools, and access to resources, all shaped Coby's social experiences.